2012
DOI: 10.5402/2012/204813
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Sealing Durability of Two Contemporary Self-Etch Adhesives

Abstract: Introduction. Sealing abilities of two self-etch adhesives were evaluated after two aging processes: storage in water and thermocycling. Materials and Methods. Cl V cavities were prepared on the buccal and lingual aspects of 48 human premolars, with cervical margins 1 mm below the CEJ. Clearfil Protect Bond (CPB) and BeautiBond (BB) (two-step and one-step self-etch adhesives, resp.) were applied, each to half of the cavities and restored with composite resin. Each group was randomly subdivided into 4 subgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
1
12
0
4
Order By: Relevance
“…The reason for the funnel-shaped lesion remains unclear, however, the pH value of SBU is approximately 2.7, mild self-etching may not allow the resin monomers to penetrate into demineralized dentin sufficiently, causing nano-spaces that remain beneath the ABRZ 35) . A thicker ABRZ was expected in the XTR group 11,37,40) , because XTR contains a fluoride-releasing component, sodium hexafluorosilicate, in the adhesive. Fluoride release from adhesives was reported to be a key factor to create thick ABRZs 8,11) .…”
Section: Discussionmentioning
confidence: 98%
“…The reason for the funnel-shaped lesion remains unclear, however, the pH value of SBU is approximately 2.7, mild self-etching may not allow the resin monomers to penetrate into demineralized dentin sufficiently, causing nano-spaces that remain beneath the ABRZ 35) . A thicker ABRZ was expected in the XTR group 11,37,40) , because XTR contains a fluoride-releasing component, sodium hexafluorosilicate, in the adhesive. Fluoride release from adhesives was reported to be a key factor to create thick ABRZs 8,11) .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies proved that thermal cycling (TC) fatigue in simulating oral conditions could accelerate the damage of ceramic materials, ascribing to the periodic stress in temperature weakening the mechanical properties. 40 In the present work, all the crowns suffered 10 000 times thermal cycling before the fracture test, for a simply simulation of the clinical condition used in many studies. 41,42 As the primary interest of this study was to investigate how the fracture behaviors of two types of monolithic lithium disilicate ceramic crowns related to different thicknesses, other inuencing factors such as mechanical aging or dynamical loading method were not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, las fallas en la interface fueron las más frecuentes, lo que demuestra un asociación evidente entre las características del material, su composición y fatiga, 25 y las características del medio bucal donde se encuentra 12 (relacionado de forma directa con la presencia de placa bacteriana, establecida mediante el índice IPV), que fueron decisivas para la presencia de defectos a nivel de los márgenes de las restauraciones, 1 sobre todo en aquellas en las que el número de superficies dentales restauradas involucró superficies proximales. 27,28 Por su composición orgánica, la dentina encontrada a nivel del límite cavo superficial de la pared gingival resulta más susceptible al deterioro por la acción de los ácidos existentes en la biopelícula dental, 26 lo que puede desencadenar lesiones a nivel pulpar, que en el estudio fueron reducidas y circunscritas a cavidades que abarcaban dos superficies, como lo corroboró el análisis radiográfico inicial.…”
Section: Discussionunclassified
“…Resulta evidente que la capacitación en el cepillado ofrecida a padres o responsables disminuye el IPV y el ISG en los niños que participaron en el estudio, lo que puede influenciar directamente en la calidad de los tratamientos realizados y resalta la importancia de llevar a cabo un proceso restaurador involucrando al paciente y a su responsable, mediante educación y motivación en la ejecución de técnicas de higiene oral. [27][28][29] El protocolo operatorio habitual frente a lesiones en dentina profunda enseñado en las escuelas de formación para odontólogos en Ecuador se basa en un correcto diagnóstico clínico y radiográfico, 12-14 seguido de la remoción total del tejido cariado, colocando o no base cavitaria o protector pulpar, dependiendo del caso, así como un material restaurador. [29][30][31][32] La elevada demanda addition to the failures caused by the aging of the restoration and the properties of the restorative material, 26 which in this study was observed by considering the five clinical criteria used, showing that the deterioration of the restoration was the least frequent, suggesting that the restorative technique was properly and carefully performed.…”
Section: Discussionunclassified